2015
DOI: 10.1371/journal.pone.0136887
|View full text |Cite
|
Sign up to set email alerts
|

The Alpha-Melanocyte-Stimulating Hormone Suppresses TLR2-Mediated Functional Responses through IRAK-M in Normal Human Keratinocytes

Abstract: Alpha-melanocyte stimulating hormone (α-MSH) is a highly conserved 13-aa neuropeptide derived from pro-opiomelanocortin by post-translational processing, which has been reported to exhibit potent anti-inflammatory activity and a wide range of immunosuppressive activities in the skin. However, the regulatory effect of α-MSH is not completely clear in cutaneous innate immunity. In this study, we investigate the functional regulation of α-MSH in TLR2-mediated inflammatory responses in normal human keratinocytes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This striking enrichment of immune-related genes in hip skin likely accounts for the propensity for many inflammatory skin diseases in non-palmoplantar skin compared with palmoplantar skin. Cluster 3 genes include immune cell-specific markers such as CD3D and CD79A , indicating a higher proportion of immune cells in hip skin, as well as immune-related genes that are expressed by skin tissue cells; these include factors such as TLR2 , involved in innate immune responses, 19 and CCL27 , which drives immune cell recruitment. 20 Cluster 3 also includes genes such as hair keratins KRT31 , KRT74 , and KRT85 related to differences in adnexal structures across the sites, as well as melanocyte markers MLANA , TYR , and TYRP1 and Langerhans cell markers CD1A and CD207 (langerin), corresponding to cell types that are more abundant in non-palmoplantar skin.…”
Section: Resultsmentioning
confidence: 99%
“…This striking enrichment of immune-related genes in hip skin likely accounts for the propensity for many inflammatory skin diseases in non-palmoplantar skin compared with palmoplantar skin. Cluster 3 genes include immune cell-specific markers such as CD3D and CD79A , indicating a higher proportion of immune cells in hip skin, as well as immune-related genes that are expressed by skin tissue cells; these include factors such as TLR2 , involved in innate immune responses, 19 and CCL27 , which drives immune cell recruitment. 20 Cluster 3 also includes genes such as hair keratins KRT31 , KRT74 , and KRT85 related to differences in adnexal structures across the sites, as well as melanocyte markers MLANA , TYR , and TYRP1 and Langerhans cell markers CD1A and CD207 (langerin), corresponding to cell types that are more abundant in non-palmoplantar skin.…”
Section: Resultsmentioning
confidence: 99%
“…Several derived peptides and analogue molecules of α ‐MSH have shown effectiveness against E. coli , methicillin‐resistant S. aureus (MRSA) and S. aureus (please refer to Table S1 for specific references). In terms of the molecule's pro‐resolutive effects, research has found that α ‐MSH treatment leads to a decrease in the phagocytosis of unopsonized E. coli and S. aureus , inhibition of nitric oxide (NO) production by RAW 264.7 cells, downregulation of TLR2 expression induced by S. aureus , and a reduction in IL‐6 levels while mitigating fever induced by LPS in rats (Huang et al, 1998; Phan & Taylor, 2013; Ryu et al, 2015; Star et al, 1995). In a mouse peritonitis model, administration of the agonist AP214 (modimelanotide) prior to zymosan injection inhibited cell infiltration via MC3R.…”
Section: Other Potential Pro‐resolving Moleculesmentioning
confidence: 99%
“…In terms of the molecule's pro-resolutive effects, research has found that α-MSH treatment leads to a decrease in the phagocytosis of unopsonizedE. coli and S. aureus , inhibition of NO production by RAW 264.7 cells, downregulation of TLR2 expression induced by S. aureus , and a reduction in IL-6 levels while mitigating fever induced by LPS in rats (Phan and Taylor, 2013;Star et al, 1995;Ryu et al, 2015;Huang and et al, 1998). In a mouse peritonitis model, administration of the agonist AP214 prior to zymosan injection inhibited cell infiltration via MC3R.…”
Section: -α-μση ανδ βαςτεριαλ ινφεςτιονςmentioning
confidence: 99%